Coupled Carbonate Chemistry - Harmful Algae Bloom Models for Studying Effects of Ocean Acidification on Prorocentrum minimum Blooms in a Eutrophic Estuary - Li, Renjian; Li, Ming; Glibert, Patricia M. (Frontiers in Marine Science, 2022)
Eutrophic estuaries have suffered from a proliferation of harmful algal blooms (HABs) and acceleration of ocean acidification (OA) over the past few decades. Despite laboratory experiments indicating pH effects on algal growth, little is understood about how acidification affects HABs in estuaries that typically feature strong horizontal and vertical gradients in pH and other carbonate chemistry parameters. Here, coupled hydrodynamic–carbonate chemistry–HAB models were developed to gain a better understanding of OA effects on a high biomass HAB in a eutrophic estuary and to project how the global anthropogenic CO2 increase might affect these HABs in the future climate. Prorocentrum minimum in Chesapeake Bay, USA, one of the most common HAB species in estuarine waters, was used as an example for studying the OA effects on HABs. Laboratory data on P. minimum grown under different pH conditions were applied in the development of an empirical formula relating growth rate to pH. Hindcast simulation using the coupled hydrodynamic-carbonate chemistry–HAB models showed that the P. minimum blooms were enhanced in the upper Bay where pH was low. On the other hand, pH effects on P. minimum growth in the mid and lower Bay with higher pH were minimal, but model simulations show surface seaward estuarine flow exported the higher biomass in the upper Bay downstream. Future model conditions with higher atmospheric pCO2 show that the P. minimum bloom size increases by ~ 3% by 2050 and ~ 5% in 2100 as pH decreases by 0.2 or 0.4, respectively. Overall the model results suggest OA will cause a moderate amplification of P. minimum blooms in Chesapeake Bay. The coupled modeling framework developed here can be applied to study the effects of OA on other HAB species in estuarine and coastal environments.